2005
DOI: 10.1007/s00280-005-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent interaction between Doxorubicin and mTHPC-mediated photodynamic therapy in murine hepatoma in vitro and in vivo

Abstract: These results indicate that Dox potentiates therapeutic efficacy of mTHPC-mediated PDT and vice versa, and the degree of potentiation is influenced by the combination schedule: administration of Dox immediately after light exposure is preferable to administration of Dox at 24 h prior to light exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Recently, novel anticancer drugs as TKIs (Dimitroff et al 1999, Liu et al 2007, mAbs (del Carmen et al 2005, Ferrario & Gomer 2006 and COX-2 inhibitors (Ferrario et al 2005) have been reported to enhance PDT-mediated toxicity. However, antagonistic responses have also been reported with PDT in combination with doxorubicin and 5FdUr (Zimmermann et al 2003, Kirveliene et al 2006. Multimodality therapy is generally considered most effective when the different monotherapies have distinct mechanisms of action (del Carmen et al 2005, Zhang et al 2005, Soffietti et al 2007).…”
Section: Egfr Targeted Drugs; Effects On Pdt and Pci Induced Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel anticancer drugs as TKIs (Dimitroff et al 1999, Liu et al 2007, mAbs (del Carmen et al 2005, Ferrario & Gomer 2006 and COX-2 inhibitors (Ferrario et al 2005) have been reported to enhance PDT-mediated toxicity. However, antagonistic responses have also been reported with PDT in combination with doxorubicin and 5FdUr (Zimmermann et al 2003, Kirveliene et al 2006. Multimodality therapy is generally considered most effective when the different monotherapies have distinct mechanisms of action (del Carmen et al 2005, Zhang et al 2005, Soffietti et al 2007).…”
Section: Egfr Targeted Drugs; Effects On Pdt and Pci Induced Protein mentioning
confidence: 99%
“…Even though PCI mainly has been used as a drug delivery system for large hydrophilic drugs with intracellular targets, the photochemical treatment (PDT) may be combined with other drugs. Increased cytotoxicity is reported after dual therapy with PDT and different chemotherapeutic drugs such as cisplatin (Nonaka et al 2002) cyclophosphamide (Casas et al 1998), 5-fluoro-2-deoxyuridine (5FdUr) (Zimmermann et al 2003), metotrexate and doxorubicin (Kirveliene et al 2006). Recently, novel anticancer drugs as TKIs (Dimitroff et al 1999, Liu et al 2007, mAbs (del Carmen et al 2005, Ferrario & Gomer 2006 and COX-2 inhibitors (Ferrario et al 2005) have been reported to enhance PDT-mediated toxicity.…”
Section: Egfr Targeted Drugs; Effects On Pdt and Pci Induced Protein mentioning
confidence: 99%
“…This suggests that DOX+Mce 6 and P-GFLG-DOX+P-GFLG-Mce 6 combinations produced similar cytotoxic intermediates with a concomitant enhancement of efficacy. Enhanced efficacy resulting from the combination of a photosensitizer and DOX has been demonstrated on various cell lines, such as Walker 256 carcinosarcoma cells (Edell and Cortese, 1988), H-MESO-1 human malignant mesothelioma cells (Brophy and Keller, 1992), murine L929 cells (Lanks et al, 1994), and murine hepatoma MH-22A (Kirveliene et al, 2006). SOS+DOX and P-GFLG-SOS+P-GFLG-DOX combinations also showed synergistic effects.…”
Section: In Vitro Growth Inhibition Of Agents In Combinationmentioning
confidence: 96%
“…One of the main disadvantages of PDT is the slow uptake of photosensitizers by tumor tissues. To enhance treatment efficiency, PDT has been successfully combined with hyperthermia, ionizing radiation, and anticancer drugs (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%